STEM-Based Scientific Learning and Its Impact on Students' Critical and Creative Thinking Skills: An Empirical Study - Astawan, I. G.; Suarjana, I. M.; Werang, B. R.; Asaloei, S. I.; Sianturi, M.; Elele, E. C. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This research aims to investigate the potential impact of STEM-based scientific learning on the critical and creative thinking skills of students at Universitas Pendidikan Ganesha in Indonesia. To achieve this goal, we conducted a quasi-experimental research design to collect data. We provided students with hands-on experiences in conducting scientific experiments to solve real-world problems related to energy and air. Data regarding students’ critical thinking skills were gathered through tests, while data about creative thinking skills were obtained by observing students’ performance in mind-mapping exercises. The collected data underwent thorough statistical analysis, including descriptive and inferential techniques. The results of this research show that students taught using the STEM-based scientific learning model outperform those taught using the conventional model (lecturing). Furthermore, inferential statistical research shows that using the STEM-based scientific learning model predicts students’ critical and creative thinking skills considerably. These results imply that using the STEM-based scientific learning model can help students improve their critical and creative thinking skills. This shows the potential to add to the body of literature on the influence of STEM-based scientific learning in developing students’ critical and creative thinking skills. Further, this study can serve as a basic reference for future studies aimed at investigating the influence of STEM-based scientific education on students from various educational backgrounds and cultural settings.